KEMATANGAN KARIR SISWA SMU BANDA ACEH DITINJAU DARI JENIS KELAMIN DAN JENIS SEKOLAH - Marpaung, Dina Naulina; Yulandari, Nucke (Psikoislamedia: Jurnal Psikologi, 2016)
The task of the development of senior high school students are choose and prepare for a career in accordance with their interests, capacity, and value. One way to measure the preparation of career choice is to look at the maturity of the individual's career. Career maturity that situation preparedness of individuals to make decisions appropriate to their career interests and potential. This study aims to look at the differences in career maturity of high school students in Banda Aceh in terms of gender and type of school. The sampling technique used is random sampling. The research sample is 344 students (172 boys and girls in senior high school, 172 boys and girls in vocational high school) in the age range 14-19 years. Data collection techniques using career maturity scale developed by the researchers. Test the hypothesis by using Independent Sample T-Test which showed a significance level of p = 0.000 (p